The Perceived Attractiveness of Chinese Products by German Consumers - A Sociopsychological Approach - Kreppel, Heidi; Holtbrügge, Dirk (Journal of Global Marketing, 2012)
The presence of Chinese companies in international markets has increased, and one of their main challenges is to overcome the negative image that Chinese products have in many countries. This study aims to shed light on how sociopsychological determinants affect the perceived attractiveness of Chinese products in Germany, using a sociopsychological approach based on social identity theory and social learning theory. The results indicate that the individual's age, level of education, occupational status, and international experience have significant effects on the perceived attractiveness of Chinese products, whereas the individual's international experience in China does not show such effects. Significant differences between different product categories are revealed. © 2012 Copyright Taylor and Francis Group, LLC.
WiSo-Import:2015-03-26:3919
Keywords: Chinese outward FDI; Chinese products; country of origin; perceived attractiveness; social identity theory; social learning theory